Ursolic acid induces apoptosis and pyroptosis in Reh cells by upregulating of the JNK signalling pathway based on network pharmacology and experimental validation - Ying Luo; Jing Xiang; Shuangyang Tang; Shiting Huang; Yishan Zhou; Haiyan Shen (Heliyon, 2023)
Objective: To explore the mechanism of ursolic acid (UA) against acute B lymphoblastic leukaemia (B-ALL) based on network pharmacological analysis, molecular docking and experimental verification. Methods: The core targets, functional processes, and biological pathways of UA in B-ALL were predicted by network pharmacology and molecular docking. The efficacy and mechanism of UA against B-ALL were verified through in vitro experiments such as cell viability assays, CCK-8 assays, LDH assays, AO/EB staining, flow cytometry, and Western blot assays. Results: Network pharmacology analysis of the core targets indicated that the effects of UA on B-ALL were related to programmed cell death (apoptosis and pyroptosis). Molecular docking results showed that FOS, CASP8, MAPK8, IL-1β and JUN were the key targets of UA against B-ALL. The MTS assay showed that UA decreased the viability of Reh cells in a concentration- and time-dependent manner. Cellular and Western blot experiments found that UA induced Reh cell apoptosis and pyroptosis by upregulating the JNK signalling pathway. Conclusions: Our findings demonstrated that UA could induce Reh cell apoptosis and pyroptosis by activating the JNK signalling pathway to exert anti-B-ALL effects. This indicates that UA may become a potential drug for the effective treatment of B-ALL.